Building EFL Lexicon for Early Childhood Learners: A Mixed Method Approach - Dr. Abrar Hussain Qureshi; Amber Saeed; Areej Fatima; Ayesha Bibi; Dr. Abdul Qayyum (Research Journal of Psychology, 2025)
This study examines the processes, techniques, and pedagogical frameworks essential for developing an English as a Foreign Language (EFL) lexicon for early childhood learners. Considering the Crucial phase of language acquisition during early childhood, cultivating a strong and age-appropriate EFL vocabulary might markedly improve learners’ subsequent linguistic proficiency and cognitive development. This research examines lexical acquisition in EFL contexts for children aged 3 to 8, utilizing theories of first and second language acquisition, schema theory, and socio-cultural learning frameworks. The study employs mixed methodologies, such as classroom observations, vocabulary evaluations, and teacher interviews, to review current lexical input models, pinpoint issues in early EFL instruction, and recommend tactics specifically designed for young learners. These encompass multimodal input, narrative techniques, total physical response (TPR), and gamified education. The Results indicate that lexical training should be integrated inside contextually rich, emotionally stimulating, and culturally pertinent content to guarantee retention and application. The paper contributes to applied linguistics by offering a practical model for EFL lexicon development grounded in interdisciplinary insights. The implications extend to curriculum designers, early childhood educators, and language policymakers aiming to enhance EFL education in multilingual environments.